Radiocarbon--a low-impact tool to study nutrient transport by soil fungi under field conditions - Czimczik, Claudia I (The New phytologist, 2005)
Here, we present a new in-situ method to study the uptake of amino acids by soil fungi. We injected 14C-labeled glycine into a marshland soil and measured the rate and the 14C signature of CO2 respired from sporocarps of Pholiota terrestris over 53.5 h and 2 m. We also determined the incorporation of glycine-C into sporocarp tissue. The 14C signature of the CO2 and tissue was quantified by accelerator mass spectrometry. After the label application, the rate of CO2 flux and its 14C signature from chambers with sporocarps were significantly higher than from chambers without sporocarps, and then declined with time. Postlabel, the 14C signature of the sporocarp tissue increased by 35 per thousand. We show that this approach can be used to study below-ground food webs on an hourly time-scale while minimizing the perturbation of competitive relationships among soil microorganisms and between plants and soil microorganisms. Additionally we show that care must be taken to avoid confounding effects of sporocarp senescence on rates and radiocarbon signatures of respired CO2